Hybrid Organic–Inorganic–Organic Isoporous Membranes with Tunable Pore Sizes and Functionalities for Molecular Separation. Issue 48 (27th September 2021) - Zhang, Zhenzhen; Simon, Assaf; Abetz, Clarissa; Held, Martin; Höhme, Anke‐Lisa; Schneider, Erik S.; Segal‐Peretz, Tamar; Abetz, Volker
Abstract: Accomplishing on‐demand molecular separation with a high selectivity and good permeability is very desirable for pollutant removal and chemical and pharmaceutical processing. The major challenge for sub‐10 nm filtration of particles and molecules is the fabrication of high‐performance membranes with tunable pore size and designed functionality. Here, a versatile top‐down approach is demonstrated to produce such a membrane using isoporous block copolymer membranes with well‐defined pore sizes combined with growth of metal oxide using sequential infiltration synthesis and atomic layer deposition (SIS and ALD). The pore size of the membranes is tuned by controlled metal oxide growth within and onto the polymer channels, enabling up to twofold pore diameter reduction. Following the growth, the distinct functionalities are readily incorporated along the membrane nanochannels with either hydrophobic, cationic, or anionic groups via straightforward and scalable gas/liquid–solid interface reactions. The hydrophilicity/hydrophobicity of the membrane nanochannel is significantly changed by the introduction of hydrophilic metal oxide and hydrophobic fluorinated groups. The functionalized membranes exhibit a superior selectivity and permeability in separating 1–2 nm organic molecules and fractionating similar‐sized proteins based on size, charge, and hydrophobicity. This demonstrates the great potential of organic–inorganic–organic isoporous membranes for high‐performance molecular separation in numerous applications. Abstract : Novel hybrid organic–inorganic–organic isoporous membranes are fabricated via sequential infiltration synthesis and atomic layer deposition within block copolymer membranes followed by addition of functional organic molecules. The membrane pore sizes are controlled by metal oxide growth in a predictive manner. The hybrid membranes exhibit superior selectivity and permeability in separating 1–2 nm organic molecules and similar‐sized proteins.